ANALISIS PERKEMBANGAN UNDANG-UNDANG HUKUM PIDANA NASIONAL: STUDI KEPUSTAKAAN TERHADAP DINAMIKA KODIFIKASI KUHP - Gunawan Widjaja; Junior B. Gregorius (INTELIGENSIA MEDIA, 2025)
This study aims to analyse the development of the National Criminal Law through a literature review of the dynamics of the codification of the Criminal Code (KUHP) in Indonesia. This study highlights the long journey of criminal law codification, from the legacy of the old KUHP based on colonial law to the birth of the new KUHP, which incorporates modern paradigms and strengthens local values and human rights principles. Through a literature review, this research describes the challenges, debates, and strategies for updating the KUHP in response to social changes and demands for justice. The analysis reveals that the reform of the KUHP is a strategic step toward a sovereign, responsive, and just national criminal law system. However, optimal implementation requires cross-sectoral collaboration, continuous education, and harmonisation with other regulations to ensure the effectiveness and consistency of criminal law enforcement in Indonesia.